Pengaruh Self-Concept Terhadap Kepercayaan Diri Peserta Didik Fase F - Salim, Elza Fahira; Mulyani, Rila Rahma; Wae, Rahmawati (Jurnal Bimbingan dan Konseling Pandohop, 2025)
This study aims to describe the self-concept and self-confidence of students, and test the effect of self-concept on students' self-confidence in phase F class of SMA Negeri 1 V Koto Timur, Padang Pariaman Regency. The research method used is descriptive correlational method with total sampling on a population of 84 students. The results showed that: 1) The self-concept of students is in the high category with a percentage of 53.57%. 2) Students' self-confidence is also in the high category with a percentage of 52.38%, but in some indicators such as optimistic, responsible, rational, and realistic, there are lower values. 3) There is a significant influence of self-concept on students' self-confidence by 57%, indicating that a more positive self-concept can increase students' self-confidence. The limitation of this study is that it does not explore the factors that influence the formation of a positive self-concept or low self-confidence in certain aspects. Further research is recommended to explore these factors for the development of more effective interventions in improving learners' self-confidence.